2016
DOI: 10.20944/preprints201609.0056.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impacts of Different Green Manure on Soil Microbial Communities and Crop Health

Abstract: Green manure could improve soil nutrients and crop production, playing a significant role in sustainable agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…showed the highest phosphate solubilization zone (16.00 mm) in PVK agar just as a documented by Lazcano et al (2013). The reports of Zhang et al (2012) and Yang et al (2016) have also shown the positive effect of organic manure on the soil microflora. Furthermore, Kohler et al (2015) showed that organic manure significantly increased shoot biomass by 64%.…”
Section: Psb Isolatesmentioning
confidence: 60%
“…showed the highest phosphate solubilization zone (16.00 mm) in PVK agar just as a documented by Lazcano et al (2013). The reports of Zhang et al (2012) and Yang et al (2016) have also shown the positive effect of organic manure on the soil microflora. Furthermore, Kohler et al (2015) showed that organic manure significantly increased shoot biomass by 64%.…”
Section: Psb Isolatesmentioning
confidence: 60%
“…Indeed, the fraction of soil carbohydrate extractable with hot water (representing about 6-8% of the total carbohydrate content), supposedly corresponding to microbial mucilage, has been shown to be correlated with aggregate stability (Haynes and Francis 1993). This could explain why in the case of our crop rotation treatment, which is known to favour microbial density and activity (Yang et al 2016), the percentages of bacterial micro-aggregates were also the highest. Mycorrhizal and saprophytic fungi are the known to be the most important soil microorganisms involved in the formation and stabilization of aggregates, but bacteria can also have profound influences on aggregation especially at the microscale (Six et al 2004).…”
Section: Discussionmentioning
confidence: 70%
“…Kao posledica nedovoljno razvijenog stočnog fonda kojim bi se mogle obezbediti potrebne količine stajnjaka, neophodno je uvođenje alternativnih organskih đubriva u cilju očuvanja plodnosti zemljišta, ali i njegovih fizičkih svojstava. S toga su međuusevi našli značajnu primenu u sideraciji, odnosno njihovom gajenju za zelenišno đubrivo, a prema Yang et al, (2016) imaju značajnu ulogu u održivoj poljoprivredi. Ćupina et al, (2004) ističu da međuusevi indirektno utiču na povećanje zdravstvenog stanja zemljišta, utičući pozitivno na strukturu zemljišta, povećavajući infiltraciju, poljski vodni kapacitet i smanjujući sabijenost zemljišta.…”
Section: Uvodunclassified